Stable microstructure in a nanocrystalline copper–tantalum alloy during shock loading - B. Chad Hornbuckle (Nature Portfolio, 2020)
Shock loading of materials alters the microstructure and considerably degrades mechanical performance. Here, shock loading of a nanocrystalline Cu–Ta alloy is found to induce minor changes to microstructure and mechanical performance, attributed to the annihilation of defects during deformation.